Impact of the Inflation Reduction Act on Patient Access and Out-of-Pocket Costs - Robertson, Justin; Zahid, Ali; Ihasz, Orsolya; York, John M. (Journal of Management Policy and Practice, 2024)
The Inflation Reduction Act (IRA) represents a recent policy enactment that will influence prescription drug pricing. This paper examines the IRA's elements and their impact on patients' access to medications, specifically around programs funded by the Centers for Medicare and Medicaid. This review analyzed grey literature on patient medication access concerning the IRA, along with the legislation itself. It finds that the IRA contains six key provisions with the potential to impact patients' access to medications and stakeholder business practices: insulin and vaccine cost share, OOP cost limits, premium stabilizations, drug negotiations, and low-income subsidy programs. Although the IRA presents cost-saving provisions, it may exert downstream effects on new drug innovation, increased medication utilization management by payers and pharmacy benefit managers (PBMs), and how healthcare providers, manufacturers, and payers/(PBMs) work together to balance patient well being with fair economic returns for all stakeholders.